Association between intentional behavioral changes and well-being during the COVID-19 pandemic - Konishi, Naoki; Kimura, Motohiro; Takeda, Yuji (Frontiers in Psychology, 2023)
The enforcement of nationwide lockdowns and social distancing measures severely restricted behavior and led to increases in stress, anxiety, and depression during the COVID-19 Pandemic. However, contrary to expectations, studies show that well-being did not decrease significantly during the Pandemic. The present study examined whether intentional increases in alternative behaviors contributed to maintaining well-being. We predicted an increase in indoor activities as alternatives to outdoor activities and that these behavioral changes contribute to maintaining well-being. Focusing on leisure activities, transport mode, and working environments, we tested these predictions in an online survey of 1,000 participants (M = 40.4 years; SD = 10.9). The results demonstrated that the decrease in outdoor leisure activities (e.g., traveling and shopping), use of public transportation, and working at office led to a reduction in well-being. It was also demonstrated that the subsequent increase in indoor leisure activities (e.g., exercising at home and online shopping) and use of a private car led to an increase in well-being, which supported our predictions. These results suggest that increasing alternative behaviors can maintain overall well-being during pandemics. These findings highlight the significance of intentional behavioral changes in maintaining well-being during pandemics.